Inadequate Therapeutic Response to a Recommended Antituberculosis Fixed-Dose Combination Regimen in an Overweight Patient with Mycobacterium bovis Infection. (January 2013) - Lloret-Linares, Célia; Mouly, Stéphane; Hoang-Nguyen, Dan-Tranh; Evans, John; Raskine, Laurent; Lopes, Amanda; Cambau, Emmanuelle; Bergmann, Jean-François; Sellier, Pierre
OBJECTIVE: To report a case of an overweight man with lymph node tuberculosis due to Mycobacterium bovis, a part of the Mycobacterium tuberculosis complex, treated with fixed-dose combination (FDC) chemotherapy. CASE REPORT: Following guidelines, according to the patient's weight (92 kg), we prescribed the maximum recommended doses of isoniazid-rifampin-pyrazinamide FDC. It led initially to underdosing, with a poor clinical outcome, justifying increased doses and a complex regimen using separate drugs (isoniazid 600 mg, rifampin 1200 mg, and levofloxacin 1000 mg) to achieve therapeutic drug concentrations and clinical response. DISCUSSION: Usually recommended doses of FDC chemotherapies may be inappropriate in overweight patients. We discuss here the different factors that may be involved in poor clinical outcomes, particularly the consequences of excess weight on drug metabolism: drug-drug interaction, FDC use, generic formulation use, intestinal malabsorption, and acetylation profile. CONCLUSIONS: Therapeutic drug monitoring in overweight patients may be useful in the clinical setting to help clinicians individualize drug therapeutic regimens and optimize drug response, adherence, and safety.